#### Answer

$(5x-1)^o=64^o
,\\
(2x)^o=26^o$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
Equate the given complementary angles to $90$, and use the properties of equality to isolate $x.$ Then substitute the value of $x$ in the following given complementary angles:
\begin{array}{l}\require{cancel}
(5x-1)^o
,\\
(2x)^o
.\end{array}
$\bf{\text{Solution Details:}}$
Since the sum of complementary angles is $90^o,$ then
\begin{array}{l}\require{cancel}
(5x-1)+(2x)=90
.\end{array}
Using the properties of equality to isolate the variable results to
\begin{array}{l}\require{cancel}
5x+2x=90+1
\\\\
7x=91
\\\\
x=\dfrac{91}{7}
\\\\
x=13
.\end{array}
Substituting $x=
13
$ in the angle $
(5x-1)^o
$ results to
\begin{array}{l}\require{cancel}
(5\cdot13-1)^o
\\\\=
(65-1)^o
\\\\=
64^o
.\end{array}
Substituting $x=
13
$ in the angle $
(2x)^o
$ results to
\begin{array}{l}\require{cancel}
(2\cdot13)^o
\\\\=
26^o
.\end{array}
Hence, the measures of the complementary angles are
\begin{array}{l}\require{cancel}
(5x-1)^o=64^o
,\\
(2x)^o=26^o
.\end{array}